Comparative analysis of structure and hardness of cast and direct metal laser sintering produced Co-Cr alloys used for dental devices. Issue 1 (18th January 2016) - Lapcevic, Ana R.; Jevremovic, Danimir P; Puskar, Tatjana M; Williams, Robert J.; Eggbeer, Dominic
Abstract : Purpose: – The purpose of this paper is to analyse structure and measure hardness of Co-Cr dental alloy samples made with two different technologies, conventional casting method (CCM samples) and additive direct metal laser sintering technology (DMLS samples), and to compare the results. Design/methodology/approach: – CCM samples were made in a conventional casting machine, using remanium 800+ Co-Cr dental alloy (Dentaurum, Ispringen, Germany). DMLS samples were fabricated out of EOS CC SP2 Co-Cr alloy (EOS, GmbH, Munich, Germany) using DMLS technology. Samples for structural analysis were plate-shaped (10 × 10 × 1.5 mm3) and for the hardness test were prismatic-shaped (55 × 10.2 × 11.2 mm3). Structure was analysed via an inverting microscope and colour metallography method. Findings: – CCM samples have a dense, irregular dendritic mesh, which is typical for the metallic phase of the Co-Cr dental alloy. DMLS alloy has a more homogenous and more compact structure, compared to CCM. Metals, the alloy basis consists of, form semilunar stratified layers, which are characteristic for the additive manufacturing (AM) technique. Hardness values of DMLS (mean value was 439.84 HV10) were found to be higher than those of CCM (mean value was 373.76 HV10). Originality/value: – There are several reports about possible use of AM technologies for manufacturing dental devices, and investigation of mechanical properties and biocompatibility behaviour of AM-produced dental alloys. Microstructure of Co-Cr alloy made with DMLS technology has been introduced for the first time in the present paper.